Impact of treatment delays on future survival outcomes in non-surgical patients with esophageal cancer in Shandong Province, China - Sun, Yindi; Zhang, Pei; Zhang, Dongqian (Frontiers in Oncology, 2024)
The treatment process of tumors in surgical patients is typically prompt and efficient, whereas non-surgical patients are more prone to treatment delay due to various factors. However, the relationship between treatment delay and survival outcomes in non-surgical Esophageal cancer (EC) patients has received limited study. This study aims to evaluate the impact of waiting time from diagnose to treatment on survival outcomes among non-surgical EC patients in Shandong Province, China. Over a 20-year follow-up period, a total of 12,911 patients diagnosed with EC and not receiving surgical intervention were identified from 2000 to 2020. The Kaplan-Meier methodology was employed to determine overall survival (OS) and cancer-specific survival (CSS). Univariate and multivariate Cox regression analyses were performed to evaluate the impact of treatment delays on future outcomes. The nonlinear association between waiting time and survival outcomes was investigated using restricted cubic spline (RCS) functions. The average delay in initiating EC treatment from the initial medical consultation for symptoms of EC was 1.18 months (95%CI=1.16-1.20). Patients with a long delay (≥3 months) in treatment demonstrated significantly lower rates of 1-, 3-, and 5-year OS and CSS compared to those with a brief delay in treatment initiation. A long delay in EC treatment independently associated with an increased risk of mortality from all causes and cancer. The association between waiting time and both all-cause and cause-specific mortality illustrated a pronounced J-shaped pattern. The prolong delay in treatment initiation significantly impacts the OS and CSS outcomes for non-surgical EC patients. Timely administration of treatment has the potential to enhance survival outcomes in patients with EC who are ineligible for surgery, including those in advanced stages without surgical options available.